PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN MATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP AL-AZHAR SYIFA BUDI PEKANBARU - Fauziah Fakhrunisa; Sehatta Saragih; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is a pre-experimental research with the static groupcomparison study design, that aims to determine whether the application of problemsolvingstrategy in mathematics learning positively affect on mathematical problemsolving ability of students of class VIII SMP Al-Azhar Syifa Budi Pekanbaru school year2015/2016. This research involved experimental and control classes that consists of 24students and 20 students. The test score of students’s mathematical problem solvingability is the data that used to test hypothesis of the research. Based on the test score,obtained the average value of mathematical problem solving ability of students inexperimental class was 3,40 and the average value of mathematical problem solvingability of students in control class was 2,16. From the Mann-Withney test, obtained thesignificance is 0,001 (less than ߙ = 0,05), it is mean that ܪ଴ has rejected and ܪଵ hasaccepted. The average value of test mathematical problem solving ability of students inexperimental class is higher than the average value of test mathematical problemsolving ability of students in control class, it can be conclude that the application ofproblem-solving strategy in mathematics learning positively affects the mathematicalproblem solving ability of students of class VIII SMP Al-Azhar Syifa Budi Pekanbaruschool year 2015/2016.Keywords: Problem-Solving Strategy, Mathematical Problem Solving Ability, Pre-experimentalResearch2